1991
DOI: 10.1016/0304-3959(91)90168-w
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects and central opioid analgesia

Abstract: Central morphine analgesia is significantly greater in male than in female rats. Since mu and delta opioid receptor subtypes have been implicated in supraspinal analgesia, the present study evaluated whether gender or adult gonadectomy altered (a) analgesia on the tail-flick and jump tests following central administration of the mu-selective agonist, [D-Ala2, Me-Phe4, Gly(ol)5] enkephalin (DAMGO) and the delta-selective agonist, [D-Ser2,Leu5] enkephalin-Thr6 (DSLET) and (b) mu1, mu2 and delta opioid receptor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(79 citation statements)
references
References 35 publications
7
70
0
2
Order By: Relevance
“…The persistence of sex differences in antinociception when opioids are administered i.c.v. [28,29], directly into the RVM [6], or directly into the PAG [31,53] also argues against a purely pharmacokinetic explanation. Thus, sex differences in opioid antinociception are probably caused by one or more pharmacodynamic factors, such as sexually dimorphic brain loci at which opioids act.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistence of sex differences in antinociception when opioids are administered i.c.v. [28,29], directly into the RVM [6], or directly into the PAG [31,53] also argues against a purely pharmacokinetic explanation. Thus, sex differences in opioid antinociception are probably caused by one or more pharmacodynamic factors, such as sexually dimorphic brain loci at which opioids act.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mu opioid receptor expression in vPAG is two-fold higher in male than in female rats [55]. Sex differences in antinociception have been observed after opioid administration to the vPAG [31,53,55] and RVM [6]; however, whereas several studies have shown that supraspinal administration of morphine or DAMGO produces greater antinociception in males [6,28,29,31], other studies have reported greater antinociception in females [53] or no sex difference [27,29]. Disagreement among such studies may result from differences in the type/intensity of the nociceptive stimulus, efficacy of the mu agonist, use of awake vs. anesthetized animals, estrous phase of females, and genotype (strain/vendor) of the rodent [11,12,38].…”
Section: Introductionmentioning
confidence: 99%
“…For example, gonadectomy of adult male rats or mice has been shown to increase (Chatterjee et al, 1982;Ali et al, 1995), decrease (Rao and Saifi, 1985;, or not affect (Kepler et al, 1989(Kepler et al, , 1991Candido et al, 1992;Islam et al, 1993;Cicero et al, 1996Cicero et al, , 2002Krzanowska and Bodnar, 1999) opioid antinociception. Gonadectomy in adult female rats also has been shown to increase (Kepler et al, 1989;Ali et al, 1995;Krzanowska and Bodnar, 1999;Terner et al, 2002), decrease (Banerjee et al, 1983), or not affect (Kepler et al, 1991;Cicero et al, 1996Cicero et al, , 2002Terner et al, 2002) opioid antinociception. The effect of adult gonadectomy on opioid antinociception has been shown to depend on subject age and opioid dose (Islam et al, 1993), as well as rodent genotype and opioid efficacy .…”
Section: Introductionmentioning
confidence: 99%
“…Age and sex-related variations in noradrenergic pain modulation pathways may account for these differences. 41 This observation may provide a new insight into the physiological mechanisms underlying the sex variation in pain perception. 42 The occurrence of morphine side effects was not increased by clonidine as reported here and detailed by others.…”
Section: Discussionmentioning
confidence: 83%